PENERAPAN METODE BESARAN PIVOT DALAM PENURUNAN RUMUS TAKSIRAN INTERVAL DARI KOEFISIEN REGRESI LINEAR SEDERHANA - Narr Herrhyanto (IKIP Siliwangi and I-MES, 2012)
Regression is the relationship between the independent variables X and Y response variables were expressed in a mathematical equation. Equations TSB will then constitute a regression equation. The linear regression equation is actually shaped Y = α + βX + ε. From the regression coefficients α and β, then β is the regression coefficient changes affecting the response variable Y.Because the value of β is usually not known, then the value will be estimated based on sample data. In this case, β assessment which will be discussed in this paper is the estimation interval. In other words, how to shape the interval estimate formula of this β. Thus, in this paper will explain how the derivation interval estimates of β. In mathematical statistics there is a method used in the valuation of this interval, ie the amount of pivot method.